The Impact of Nutrion Education for Health Workers on Lactation Knowledge and Healthy Dietary Practices - Harnaningsi; Yun Diniaty Rosidi, Indah; Lestari Salim, Ika (Napande: Jurnal Bidan, 2025)
Background: During the postpartum period, nutritional requirements increase significantly, particularly for breastfeeding mothers. The increase is approximately 25%, as the body needs additional energy for maternal recovery and adequate milk production to support infant health. Nutritional adequacy is determined not only by the quantity of food consumed but also by the quality of nutrients. Methods: This study employed a pre-experimental design with a One-Group Pretest–Posttest approach. Data were collected using questionnaires administered before and after the intervention, and were analyzed using descriptive statistics and inferential analysis through paired t-tests. Results: The findings revealed a significant improvement in postpartum mothers’ knowledge following the intervention, with a 28% increase observed. Statistical analysis indicated that nutrition education delivered by healthcare professionals had a significant effect on enhancing lactation knowledge and promoting healthy dietary practices among breastfeeding mothers (p-value 0.001 < 0.05). Conclusion: Nutrition education by health workers has proven effective in improving lactation knowledge and healthy dietary practices among breastfeeding mothers. These findings highlight the need to integrate educational interventions into maternal and child health programs, particularly at community health posts and primary care services